The Product Development Strategy To Increase Business Competitiveness Of PT Lambang Jaya Lampung Selatan - M Daffa Arrizky; Farida Efriyanti (International Journal of Economics, Business and Innovation Research, 2024)
PT. Lambang Jaya South Lampung has quite a lot of competitors in the field of agricultural equipment engineering, factory construction, and providing factory equipment maintenance services. Of course it has many competitors in its field, especially PT Lambang Jaya which is located in the South Lampung area which is an industrial area in Lampung. The approach used in this research is a qualitative approach with descriptive analysis, Data Analysis Techniques. Data analysis in qualitative research is carried out during data collection as stated by Miles and Huberman, namely: data reduction, data display, withdrawal. Conclusions (concluding drawing), in this research results were obtained. In a proactive approach, the company carries out continuous research and development to anticipate future consumer needs and improve product quality. They also adapted marketing strategies that focused on understanding consumer needs and adjusting prices accordingly. Meanwhile, in a reactive approach, companies respond to market conditions or competitors with defensive, imitative and second but better strategies. They protect themselves from threats from competing products by maintaining the security of research and development results, as well as conducting research on competitor products to improve the quality of their own products